Innate Immune Responses in Leprosy - Pinheiro, Roberta Olmo; Schmitz, Veronica; Silva, Bruno Jorge de Andrade; Dias, André Alves; de Souza, Beatriz Junqueira; de Mattos Barbosa, Mayara Garcia; de Almeida Esquenazi, Danuza; Pessolani, Maria Cristina Vidal; Sarno, Euzenir Nunes (Frontiers in Immunology, 2018)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that may present different clinical forms depending on host immune response to bacilli. Several studies have clarified the role of various T cell populations in leprosy; however, recent evidences suggest that local innate immune mechanisms are key determinants in driving the disease to its different clinical manifestations. Leprosy has become an ideal model to study the immunoregulatory role of innate immune molecules and its interaction with nervous system, which can affect homeostasis and contribute to the development of inflammatory episodes during the course of the disease. Macrophages, dendritic cells, neutrophils, and keratinocytes are the major cell populations studied and the comprehension of the complex networking created by cytokine release, lipid and iron metabolism, as well as antimicrobial effector pathways might provide targets for therapeutic intervention in modulating leprosy.